Incidence, risk factors, and outcomes of non-fatal work-related injuries among older workers: A review of research from 2010 to 2019. (June 2020) - Stoesz, Brenda; Chimney, Katherine; Deng, Connie; Grogan, Harrison; Menec, Verena; Piotrowski, Caroline; Shooshtari, Shahin; Turner, Nick
Highlights: We examined the literature published between 2010 and 2019 on older workers' safety. Focus of literature varies on attention paid to modifiable risk factors, non-modifiable risk factors, and outcomes. Differences exist in older workers' injuries by occupation. Compared to younger workers, the incidence of work-related injuries was lower among older workers. Compared to younger workers, older workers endured more severe and more costly work-related injuries. Abstract: We reviewed the literature on older workers and work-related injuries published between 2010 and 2019. A review of empirical research during this period yielded 63 original research articles meeting the inclusion criteria. Across these studies, we found differences in work-related injuries among older workers by occupation, and differences in attention paid to modifiable risk factors, non-modifiable risk factors, and outcomes of work-related injuries among older workers. In general, compared to younger workers, the incidence of work-related injuries was lower among older workers, yet older workers endured more severe and more costly work-related injuries. Taken together, this review highlighted factors for consideration in the prevention of work-related injuries among older workers.